Carbapenemase Production and Epidemiological Characteristics of Carbapenem-Resistant Klebsiella pneumoniae in Western Chongqing, China - Huang, Wan; Zhang, Jisheng; Zeng, Lingyi; Yang, Chengru; Yin, Lining; Wang, Jianmin; Li, Jie; Li, Xinhui; Hu, Kewang; Zhang, Xiaoli; Liu, Beizhong (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Background: This study aimed to determine the molecular characteristics of carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates in a hospital in western Chongqing, southwestern China. Methods: A total of 127 unique CRKP isolates were collected from the Yongchuan Hospital of Chongqing Medical University, identified using a VITEK-2 compact system, and subjected to microbroth dilution to determine the minimal inhibitory concentration. Enterobacteriaceae intergenic repeat consensus polymerase chain reaction and multilocus sequence typing were used to analyze the homology among the isolates. Genetic information, including resistance and virulence genes, was assessed using polymerase chain reaction. The genomic features of the CRKP carrying gene blaKPC-2 were detected using whole-genome sequencing. Results: ST11 was the dominant sequence type in the homology comparison. The resistance rate to ceftazidime-avibactam in children was much higher than that in adults as was the detection rate of the resistance gene blaNDM (p < 0.0001). Virulence genes such as mrkD (97.6%), uge (96.9%), kpn (96.9%), and fim-H (84.3%) had high detection rates. IncF (57.5%) was the major replicon plasmid detected, and sequencing showed that the CRKP063 genome contained two plasmids. The plasmid carrying blaKPC-2, which mediates carbapenem resistance, was located on the 359,625 base pair plasmid IncFII, together with virulence factors, plasmid replication protein (rep B), stabilizing protein (par A), and type IV secretion system (T4SS) proteins that mediate plasmid conjugation transfer. Conclusion: Our study aids in understanding the prevalence of CRKP in this hospital and the significant differences between children and adults, thus providing new ideas for clinical empirical use of antibiotics.